Cost-utility analysis of a universal pneumococcal vaccination programme for older adults in Norway - Liv Solvår Nymark; Jacob Dag Berild; Trude Marie Lyngstad; Brita Askeland Winje; Didrik Frimann Vestrheim; Ingeborg Aaberge; Lene Kristine Juvet; Ellen Wolff (Taylor & Francis Group, 2022)
The aim of this study was to establish whether a universal pneumococcal vaccination for older adults in Norway is likely to be cost-effective from the perspective of the health care provider. A decision tree model developed by the Public Health Agency of Sweden was adopted to the Norwegian setting. Two cohorts, consisting of 65-year-olds and 75-year-olds grouped into vaccinated and unvaccinated, were followed over a 5-year time horizon. In the base case, the 23-valent polysaccharide vaccine (PPV23) was used while the 13-valent pneumococcal conjugate vaccine (PCV13) was included in scenario analyses only. The costs and health benefits (measured in quality adjusted life years (QALY) gained) were compared in the two cohorts between the vaccinated and unvaccinated groups. The impact of indirect effects of the vaccine, such as herd immunity and serotype replacement, were not investigated. The relative importance of change in price was assessed by performing one-way sensitivity analyses. Under base-case assumptions, the programme for the 75-year-old cohort is expected to be cost-effective from the health care perspective at the current pharmacy purchasing price and at 75% vaccination coverage as it falls below the lower end of the cost-effectiveness threshold range (NOK 9467/EUR 964). In comparison, for the 65-year-old cohort the cost per QALY gained is approximately NOK 780 206 (EUR 79 451) under the base-case assumptions which falls within the acceptable ranges in a Norwegian context for both the 65- and 75-year-old cohorts. There is no exact cost-effectiveness threshold in Norway. However, introducing a vaccination programme against pneumococcal disease for 65-year-olds and 75-year-olds in Norway is likely to fall within the acceptable cost-effectiveness threshold range.